Systemic ceramide accumulation leads to severe and varied pathological consequences. Issue 6 (16th May 2013) - Alayoubi, Abdulfatah M.; Wang, James C. M.; Au, Bryan C. Y.; Carpentier, Stéphane; Garcia, Virginie; Dworski, Shaalee; El‐Ghamrasni, Samah; Kirouac, Kevin N.; Exertier, Mathilde J.; Xiong, Zi Jian; Privé, Gilbert G.; Simonaro, Calogera M.; et al.
Abstract Farber disease (FD) is a severe inherited disorder of lipid metabolism characterized by deficient lysosomal acid ceramidase (ACDase) activity, resulting in ceramide accumulation. Ceramide and metabolites have roles in cell apoptosis and proliferation. We introduced a single‐nucleotide mutation identified in human FD patients into the murine Asah1 gene to generate the first model of systemic ACDase deficiency. Homozygous Asah1P361R/P361R animals showed ACDase defects, accumulated ceramide, demonstrated FD manifestations and died within 7–13 weeks. Mechanistically, MCP‐1 levels were increased and tissues were replete with lipid‐laden macrophages. Treatment of neonates with a single injection of human ACDase‐encoding lentivector diminished the severity of the disease as highlighted by enhanced growth, decreased ceramide, lessened cellular infiltrations and increased lifespans. This model of ACDase deficiency offers insights into the pathophysiology of FD and the roles of ACDase, ceramide and related sphingolipids in cell signaling and growth, as well as facilitates the development of therapy. →See accompanying article http://dx.doi.org/10.1002/emmm.201302781